THE URGENCY FOR THE ESTABLISHING A VICTIM TRUST FUND IN SEXUAL VIOLENCE CRIMES IN INDONESIA - Beniharmoni Harefa; Salma Agustina (Universitas Syiah Kuala, 2022)
This article aims to examine the importance of the Victim Trust Fund in handling criminal cases of sexual violence in the Indonesian criminal law system and its comparison to the Victim Trust Fund in the United States. This article uses a normative juridical research with a statutory, a conceptual and a comparative approach. The position of victims in the Victim Trust Fund is very important for the criminal justice system in Indonesia because it creates a firm and a binding justice. The Victim Trust Fund is a compensation system in Indonesia apart from restitution and compensation where it is necessary to establish a victim assistance fund management institution to be able to manage the funds allocated to victims.